Insights Into Extracellular Vesicles as Biomarker of NAFLD Pathogenesis - Garcia-Martinez, Irma; Alen, Rosa; Rada, Patricia; Valverde, Angela M. (Frontiers in Medicine, 2020)
Nonalcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease around the world estimated to affect up to one-third of the adult population and is expected to continue rising in the coming years. Nonalcoholic fatty liver disease is considered as the hepatic manifestation of the metabolic syndrome because it is strongly associated with obesity, insulin resistance, type 2 diabetes mellitus, and cardiovascular complications. Despite its high prevalence, factors leading to NAFLD progression from simple steatosis to nonalcoholic steatohepatitis, cirrhosis, and, ultimately hepatocellular carcinoma remain poorly understood. To date, no treatment has proven efficacy, and also no reliable method is currently available for diagnosis or staging of NAFLD beyond the highly invasive liver biopsy. Recently, extracellular vesicles (EVs) have emerged as potential candidate biomarkers for the diagnosis of NAFLD. Extracellular vesicles are circulating, cell-derived vesicles containing proteins and nucleic acids, among other components, that interact with and trigger a plethora of responses in neighbor or distant target cells. Several mechanisms implicated in NAFLD progression, such as inflammation, fibrosis, and angiogenesis, all related to metabolic syndrome–associated lipotoxicity, trigger EV production and release by liver cells. As hepatocytes represent ~80% of the liver volume, in this review we will focus on hepatocyte-derived EVs as drivers of the interactome between different liver cell types in NAFLD pathogenesis, as well as in their role as noninvasive biomarkers for NAFLD diagnosis and progression. Based on that, we will highlight the research that is currently available on EVs in this topic, the current limitations, and future directions for implementation in a clinical setting as biomarkers or targets of liver disease.